Godliness and Greed: Shifting Christian Thought on Profit and Wealth - Worden, Skip (Lexington Books, 2010)
Traditional scholarship often points to the Calvinists and Max WeberOs writing on the Protestant ethic as the catalysts to changing Christian attitudes concerning profit-seeking and wealth. Author Skip Worden argues that the seeds of this change occurred centuries earlier. From the beginning of the Commercial Revolution to the fifteenth-century Renaissance, he shows that the predominant Christian thought on economics went through a fundamental shift, becoming favorable toward profit-seeking and wealth-holding. Worden discusses this dramatic change and explains how the general antagonism toward the pursuit of wealth before the Commercial Revolution transformed into Protestant theologians' fighting against the prevailing view of a pro-wealth paradigm during the fifteenth century. Worden contends that the shift away from the Patristic view of wealth occurred well before the addition of the Calvinist spirit of capitalism and the Puritan work ethic into Christian economic vernacular. Drawing on Plato, Cicero, and Augustine, early Protestant theologians unsuccessfully sought to check the rising dominance of the pro-wealth Christian paradigm, which they believed had been pushed too far. These theologians of the sixteenth and seventeenth century felt it was too close to advocating love of gain itself, something too close to the sin of greed. How well the Reformation succeeded can be assessed by WordenOs insightful concluding study of John D. Rockefeller, the ascetic steward of GodOs Gold in the form of monopoly.